The Wrist Joint Complex: Anatomical, Physiological and Biomechanical Aspects, Characteristics, Classification, and Treatment of Distal Radius Fractures - Carlos Eduardo Medina Gonzalez; Mikhail Benet Rodríguez; Fernando Marco Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
The distal radius fracture or wrist, is one of the most common fractures in children and in adults, especially in women. The causes are different, in the children is mainly due to sports injuries, the latter primarily related disorders including elderly osteoporosis. The aim of this work is to do review of the distal radial fracture in which elements of their history, different types of classifications and very updated aspects of the management of patients with this injury is included, including the use of external fixators. The authors address this issue with an extensive literature review and images and figures taken from the literature and made by the authors themselves.